Effects of Joule Heating and Viscous Dissipation on MHD Flow and Heat Transfer of Casson Fluid over a Stretching Cylinder in a Porous Medium - M. Mishra, D. Panda, K. Swain (International Journal of Advanced Science and Technology, 2020)
An investigation is made to study the effects of Joule heating and viscous dissipation on MHD flow, heat and mass transfer of Casson fluid over a stretching cylinder in a saturated porous medium in presence of uniform heat source/sink. The governing PDEs are converted into non-linear and coupled ODEs by the help of suitable similarity transformations. The effective shooting technique is adopted to solve these ODEs. The influences of parameters related to the flow phenomena are discussed via graphs and tables. The physical quantities of engineering interest such as skin friction coefficient, Nusselt number and Sherwood number are examined through table. The numerical solution reveals that temperature of the Casson fluid decreases with the higher values of Casson fluidity; this may have a therapeutic application to control the temperature of blood or any biological fluid. Schmidt number and solutal conjugate parameter has opposite effects on concentration distribution.Keywords: Casson fluid, stretching cylinder, Joule heating, viscous dissipation, uniform heat source/sink.